KIF17 maintains the epithelial phenotype of breast cancer cells and curbs tumour metastasis. (1st November 2022) - Li, Tianfu; Zhai, Duanyang; Zhang, Mengmeng; Ye, Runyi; Kuang, Xiaying; Shao, Nan; Bi, Jiong; Lin, Ying
Abstract: Kinesin superfamily motor protein 17 (KIF17) was previously identified downregulated in breast cancer and correlated with patient prognosis. However, its pathophysiological role in tumours remains unknown. Here, we confirmed that KIF17 was significantly under-expressed in breast cancer tissues and low KIF17 expression correlated with poor outcomes in patients with breast cancer. In vitro and in vivo experiments demonstrated that KIF17 overexpression in breast cancer cell lines significantly inhibited breast cancer invasion and metastasis. By establishing the lung metastatic MDA-MB-231 cell lines, we found a transient silence of KIF17 during the initiation of breast cancer metastasis. Further experiments revealed that KIF17 might suppress metastasis by regulating the level of acetylated tubulin to maintain cytoskeleton stability. Eventually, we found that the low expression of KIF17 in breast cancer is regulated by DNMT1-mediated 5-mC DNA methylation and epigenetic silencing. Decitabine can effectively improve the expression level of KIF17 in breast cancer cells. Our study demonstrates that KIF17 mediates microtubule acetylation to maintain the stability of microtubules, thereby inhibiting tumour invasion and metastasis. Highlights: KIF17 is downregulated in breast cancer and serves as a tumour suppressor that correlates with the prognosis of breast cancer patients. KIF17 maintains the epithelial phenotypes of tumour cells and inhibits tumour invasion and metastasis by mediating MT acetylation. The transcriptional regulation of KIF17 in breast cancer is mainly regulated by DNMT1-meditated epigenetic silencing via 5-mC DNA methylation. The use of DNA methylase inhibitors can effectively increase the expression level of KIF17 in tumour cells, providing the basis for the potential application value of epigenetic drugs in the treatment of patients with breast cancer resistant to MT stabilisers.